Pelatihan Strategi Manajemen Burnout untuk Meningkatkan Kemampuan 4C (Creativity, Critical Thinking, Communication, Collaboration) Bagi Guru dan Tenaga Kependidikan di SMP Muhammadiyah 2 Banjarbaru - Eka Sri Handayani; Akhmad Rizkhi Ridhani; Endang Pratiwi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service activity aims to help teachers and education staff manage burnout while improving the ability of the 4Cs (Creativity, Critical Thinking, Communication, and Collaboration) in the school work environment. The training was held at SMP Muhammadiyah 2 Banjarbaru with the involvement of 11 participants, using a participatory approach that included interactive lectures, group discussions, reflections, and role play simulations. The main objective of this activity is to build the adaptive capacity and psychological well-being of educators through strengthening 21st century skills. The evaluation was carried out by comparing burnout scores before and after the training. The results showed a significant decrease in the average burnout score from 71.6 to 57.4, or by 14.2 points. This decline reflects an improvement in participants' psychological well-being and adaptive ability in the face of work pressure. In addition, training also has a positive impact on improving creative thinking, collaborative, and positive communication skills in the context of school work. These findings show that participatory-based interventions are effective in building a healthier and more productive work environment for educators. This activity recommends replicating similar training in other educational institutions as a preventive and promotive strategy to overcome burnout and strengthen teachers' professional competence in facing contemporary educational challenges.